Bisphosphonates in the Management of Patients with Postmenopausal Osteoporosis; Back to the Future - Socrates E. Papapoulos; Polyzois Makras (Pharmaceuticals)
Osteoporosis is a chronic disease associated with significant morbidity and mortality and requires long-term therapy. Efficacious and well-tolerated treatments are available, but their effect is either short-lived or lost following their discontinuation. The exception is bisphosphonates that reduce bone resorption and turnover, can be administered in regimens ranging from once-daily to once-yearly, and have been shown in randomized clinical trials to reduce the incidence of all osteoporotic fractures, but their effect persists following their discontinuation. This is due to their property of being taken-up selectively by the skeleton and being slowly released following treatment arrest. This property allows the discontinuation of bisphosphonate treatment for different periods of time, the so-called drug holiday, which reduces the risk of rare adverse events while maintaining the effect; an action particularly important for patients at very high risk of fractures for whom sequential therapy with different agents is currently advised. Thus, bisphosphonates, apart from being the treatment of choice for certain groups of patients, are also indispensable for the consolidation and maintenance of the gains of all other treatments, providing, in addition, the opportunity of temporary treatment arrest. Most patients with postmenopausal osteoporosis will, therefore, receive bisphosphonate at some stage during therapy of their disease, regardless of their initial fracture risk.